Small scale boilover and visualization of hot zone - Wan Kamarudin, W.N.I. (Elsevier Ltd, 2016)
Experimental studies of boilover were conducted in small scale rig at Universiti Teknologi PETRONAS (UTP), Malaysia and Loughborough University, United Kingdom. The study at UTP was aimed to demonstrate the ability of conducting tests at a smaller scale to simulate the boilover phenomenon. At Loughborough University, a novel laboratory scale rig was designed and built in order to obtain visual records of fuelsâ behaviour in a pool fire. The ultimate objective of these studies is to develop a greater understanding of boilover pertaining to fires involving the contents of storage tanks. Fuel mixtures containing light and heavy components were burnt as to study the feasibility of reproducing hot zone formation and boilover in a smaller scale and a safe environment. Boilover occurred after certain period of burning. It is found that thickness of the hot zone changed with time. It is also found that the time needed to start boilover increased when fuel thickness increased. The visualization of the fuel behaviour during the experiments was obtained to better understand the formation and growth of hot zone, the boiling of water layer and hence the boilover occurrence. Based on the data analysis and the photographs recorded from the experiments, the laboratory scale experimental rig could be used to simulate the hot zone formation mechanism and the boilover event safely and successfully. Such information are important for the understanding towards boilover phenomenon. Â© 2016 Elsevier Ltd